Pengelolaan Terbitan Berseri Di Perpustakaan Sekolah Man 2 Palembang - Rendy Andrean (UIN Sumatera Utara, 2018)
The purpose of this research is: (a) to describe the management of serial publication in MAN 2 Palembang library, (b) to describe the service of serial publication in libraries MAN 2 Palembang, (c) to describe SNI serialized in MAN 2 Palembang library. The method used in this study using descriptive approach through observation and interview conducted directly in the library MAN 2 Palembang. The technique used in collecting data is through observation and direct interview with Mrs. Dra. Lisnawati as head of MAN 2 Palembang library. Keywords: serial publications, school libraries, periodical publications